The Indirect Ways of Expression of the Speech Act of Request - ADAMYAN, VERA (Bulletin of Yerevan University H: Russian Philology, 2021)
The paper describes the morphological and syntactic features of the expression of the speech act of request, in particular, the author made an attempt to identify indirect ways of influencing on the addressee. The author singles out the lexical and syntactical constructions typical for the speakers of the Russian language by analysis of discourses taken from the modern literature, in particular, there are differentiated interrogative constructions, narrative and declarative sentences.